From Biopiracy to Fair Benefit Sharing: Evaluating the Impact of IP and Genetic Resources Treaty with reference to Ahom Tribes of Assam (International Journal of Food and Nutritional Sciences, 2022)
Abstract India is rich in biodiversity, flora and fauna. It is also rich in cultural diversity and many indigenous communities reside together.